Spectral behavior of novel benzanthrone probe in model membranes - Zhytniakivska, O.A.; Kutsenko, O.K.; Trusova, V.M.; Gorbenko, G.P.; Kirilova, E.M.; Kirilov, G.K.; Kalnina, I. (Харьковский Национальный Университет им. В.Н.Каразина, 2011)
The present study was undertaken to evaluate the sensitivity of a newly synthesized benzanthrone dye to the changes in physicochemical properties of lipid bilayer. It was shown that the dye under study is non- emissive in buffer but exhibites strong fluorescence in lipid phase. Partitioning of AM15 into model membranes composed of zwitterionic lipid phosphatidylcholine (PC) and its mixtures with anionic lipid cardiolipin and cholesterol was followed by significant increase of fluorescence quantum yield. Analysis of the partition coefficients showed that inclusion of cardiolipin and choleterol into phosphatidylcholine bilayer gives rise to the decrease of AM15 incorporation into lipid phase compared to the neat phosphatidylcholine membrane. It is assumed that AM15 resides in the hydrophobic bilater region, being oriented parallel to the lipid acyl chains.
Keywords: benzanthrone dye; liposomes; phosphatidylcholine; cardiolipin; cholesterol; lysozyme